Efforts to Strengthen the Indonesian Insurance Sector through the Policy Guarantee Program - Nuzul Quraniati Rohmah (PT. Anagata Sembagi Education, 2024)
The development of the financial sector in Indonesia has increased positively, but the insurance sector is still constrained by low penetration rates and default cases that threaten public confidence. To overcome these problems, the Policy Guarantee Program was implemented as an effort to protect policyholders and strengthen the insurance sector. This article analyzes the relevant laws and regulations, the phenomenon of insurance company defaults, and policyholder protection mechanisms in the context of insurance company bankruptcy. The Policy Guarantee Program, mandated in the Insurance Law, aims to guarantee the return of policyholders' rights against liquidating insurance companies. Although there is no detailed information on the operational scheme, some countries such as Japan have successfully implemented similar programs with satisfactory results, which can be a motivation for Indonesia to improve the insurance climate through a policy guarantee program.